POTENSI BUDIDAYA TANAMAN SONOKELING MELALUI PEMBERDAYAAN KELOMPOK BM CREATIVE WOODS DI DESA GIRIHARJO, KECAMATAN PANGGANG, KABUPATEN GUNUNG KIDUL - Kinanti Indah Safitri (Jurnal Gama Societa, 2019)
The object of this research in Giriharjo Village which has potential trees that can be used for making wooden crafts.  The kind of tree is sonokeling. Sonokeling has a strong texture with brownish purple fibers. Sonokeling wood is high quality wood and it used for home decor, wooden watch, flashdisk cover and various other products. This research was carried out on since October 2018 – Mei 2019. The research method used qualitative- study case approach. The  data collection technique through in depth interview, observation and documentation .  The research result showed that in Giriharjo Village , there are BM creative woods group that make wooden crafts. However, this group has a problem to continue production process because the human resources have a lack of interest and constraints in marketing strategy. Therefore, innovation is needed that includes: institutional strengthening, cultivation sonokeling plants and internalization effective marketing strategy.  Keywords: Empowerment, Institution, Cultivation, Marketing.